XXVII International Symposium on Biomechanics in Sports (2008)
The 27th annual ISBS conference is being held in Limerick, Ireland. As Ireland's 'sporting city' it is a natural home for a conference which promotes conversation and collaboration between scientists and coaches and enables us to disseminate information to the sporting community. Limerick embraces its sporting nature and the University of Limerick focuses this nature with Ireland's foremost facilities for sport and sports science education.